Patterns of fertility in the two Red Sea Corals Stylophora pistillata and Acropora humilis - MOHAMMED S.A. AMMAR; AHMED H. OBUID-ALLAH; MONTASER A.M. AL-HAMMADY (Smujo International, 2012)
Abstract. Ammar MSA Obuid-Allah AH, Al-Hammady MAM. 2012. Patterns of fertility in the two Red Sea Corals Stylophora pistillata and Acropora humilis. Nusantara Bioscience 4: 62-75. Patterns of fertilities (total testes and total eggs) for the hermatypic coral Acropora humilis were lower than those in Stylophora pistillata at the four studied sites. Site 3 (El-Hamraween harbor), the site impacted with phosphate, recorded the highest annual mean of testes number and egg number in the two studied species Acropora humilis and S. pistillata. However, site 1, the site impacted with oil pollution and fishing activities, recorded the lowest annual mean of testes number, total testes, egg number and total egg for the two studied species. Thus, phosphorus enrichment seems to be considerably less destructive than oil pollution, and thus may represent an ‘eco-friendly’. Testes were observed fully of sperms during winter season in the sectioned polyps of A. humilis, while eggs were detected during autumn and winter. However, the lack of eggs in S. pistillata occurred only during spring season at all the studied sites. In the studied coral species, the ova were developed first before spermeria. The breeding season of coral reefs differs in both different localities and different species extending from December to July in the northern Red Sea, Gulf of Aqaba and Southern Red Sea (the present study). While in A. humilis, the breeding season extends from February to June in the Great Barrier Reef, in the Gulf of Aqaba and in Hurghada (the present study). Tough control, public awareness and continuous shore patrolling to the activities of oil pollution and fishing activities at the vicinity of site 1 (Ras El-Behar) are urgent. Although existing corals may continue to grow and survive in an area with elevated nutrients levels, it is essential to maintain water quality on coral reefs within ecologically appropriate limits to ensure successful reproduction of coral and provide recruits for the long- term maintenance and renewal of coral populations.